The State of Knowledge of Harmful Algal Blooms of Margalefidinium polykrikoides (a.k.a. Cochlodinium polykrikoides) in Latin America - López-Cortés, David J.; Núñez Vázquez, Erick J.; Dorantes-Aranda, Juan J.; Band-Schmidt, Christine J.; Hernández-Sandoval, Francisco E.; Bustillos-Guzmán, José J.; Leyva-Valencia, Ignacio; Fernández-Herrera, Leyberth J. (Frontiers in Marine Science, 2019)
The marine dinoflagellate Margalefidinium polykrikoides is a harmful species that has affected aquaculture, fisheries and tourism activities. It produces reactive oxygen species (ROS) as well as hemolytic and neurotoxic-like substances that have been associated with mass mortalities of marine organisms. It has a tropical and subtropical distribution that has mainly affected Asia and North America. The economic impacts for aquaculture industries have been estimated to be up to US$140M. In Latin America, no economic estimates have been performed. Harmful algal blooms by M. polykrikoides are more frequent in Mexico and Central America. Proliferations of this dinoflagellate are associated with winds, upwelling, convergence areas, local convection of seawater, and eutrophication of coastal areas by nitrogen and phosphorus compounds from rainwater runoff, as well as agricultural and aquaculture activities, into coastal waters. Eco-physiological and toxicological studies have provided detailed descriptions of the growth of algal strains from these regions and the harmful effects on fish and shrimp, as well as the role the production of ROS and polyunsaturated fatty acids in their toxicity. It is also possible that M. polykrikoides has an ecological role in the regulation of blooms of other harmful algae. In this contribution, we review the records of harmful algal blooms of M. polykrikoides in Latin America and the research that has been conducted with this species.